Penggunaan Aplikasi Edmodo Dalam Pembelajaran Sejarah Dalam Meningkatkan Aktivitas dan Hasil Belajar - juliandry kurniawan junaidi; Pramitha Sari (Bakaba : Jurnal Sejarah, Kebudayaan dan Kependidikan, 2021)
This study aims to determine the use of power point media in the Edmodo electronic learning application in improving learning activities and student learning outcomes in history subjects for students of class X.2 SMK SMTI Padang. This research is a Classroom Action Research (CAR) in collecting data the authors use observation sheets and give tests at the end of each cycle. Observation sheets for learning activity data and giving tests for student learning outcomes data. The research was conducted in two cycles. From the results of the first cycle, it shows that learning activities are 19.64% after the second cycle there is an increase in student learning activities to 25%, while for learning outcomes there is also an increase in the first cycle, it is found that 60% of students complete data in the second cycle, an increase of 97.14% students complete. From the results I and II based on these two variables, it shows an increase in activity and learning outcomes using the Edmodo application in history lessons in class X2 SMK SMTI Padang.